Moderation and Modernism in India’s Nuclear Policy: Post 1974 Era - Singh, Dr. Rajkumar; Kumari, Hemlata (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
India, after its first nuclear explosion in 1974 moved to modernize and moderate nuclear policy as security environment in the region deteriorated further due to China, pursuing a strategy of containing India by using Pakistan as a surrogate, had supplied technology nuclear materials and warhead designs for the Pakistani bomb. Clearly with Chinese help Pakistani detonated six nuclear devices as follow up of India’s repeat detonation in the second week of May 1998. This development changed the security environment in South Asia forever and this time India convinced the international community that it would not become a destabilising nuclear force in the international system. Thus, in the post-1998 era India adopted two concepts, (i) No first use for attack or war and (ii) Credible minimum deterrence. As a step further in the direction India also signed with the US a nuclear deal under which it agreed to separate its civil and military nuclear facilities under international safeguard and supervision. The paper analyses the evolution of India’s nuclear capability in regional and global contexts.